A voxel-level resting-state fMRI study on patients with alcohol use disorders based on a power spectrum slope analysis method - Ruan, Xia; Song, Zhiyan; Yu, Tingting; Chen, Jun (Frontiers in Neuroscience, 2024)
Background: Earlier neuroimaging investigations showed that abnormal brain activity in patients with alcohol use disorder (AUD) was frequency dependent. However, there is lacking of a comprehensive method to capture the amplitude of multi-frequency bands directly. Here, we used a new method, the power spectrum slope (PSS) to explore abnormal spontaneous activity of brain in patients with AUD.Methods: Thirty-three AUD patients and 29 healthy controls (HCs) enrolled in this study. The coefficient b and the power-law slope b' were calculated and compared between two groups. We also used the receiver operating characteristic (ROC) curve to examine the ability of the PSS analysis to distinguish between AUD and HCs. We next examined the correlation between PSS difference in the brain areas and the severity of alcohol dependence.Thirty AUD patients and 26 HCs were retained after head motion correction.The two metrics of PSS values increased in the left precentral gyrus in AUD patients.The area under the curve values of PSS differences in the specific brain area were at the range of 0.836-0.844 with sensitivities of 83.3%-86.7% and specificities of 73.1%-76.9%. The Michigan Alcoholism Screening Test (MAST) and Alcohol drinking scale (ADS) scores were not significantly correlated with the PSS values in the specific brain area.As a novel method, the PSS can well detect abnormal local brain activity in the AUD patients and may become an alternative power spectrum analysis method in future fMRI studies.